2021
DOI: 10.2196/30151
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Remission Rate of Chronic Headache Comparing Video and Face-to-Face Consultations by Neurologist: Randomized Controlled Trial

Abstract: Background Chronic headache causing severe headache-related disability for those affected by the disease is under- or misdiagnosed in many cases and therefore requires easy access to a specialist for optimal health care management. Objective The goal of the research is to determine whether video consultations are noninferior to face-to-face consultations in treating chronic headache patients referred to a specialist in Northern Norway. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 50 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…Nine studies (20 26,28,29) reported on treatment efficacy and headache status using a broad variety of parameters. This included headache days per month, medication use, Migraine Disability Assessment (MIDAS), Headache Impact Test (HIT-6), Visual Analogue Scale (VAS), subjective changes in headache status and remission rate of chronic headache.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies (20 26,28,29) reported on treatment efficacy and headache status using a broad variety of parameters. This included headache days per month, medication use, Migraine Disability Assessment (MIDAS), Headache Impact Test (HIT-6), Visual Analogue Scale (VAS), subjective changes in headache status and remission rate of chronic headache.…”
Section: Resultsmentioning
confidence: 99%
“…The study investigated follow-up teleconsultations in an outpatient setting. Another study (26) looked at a subgroup of patients who had remission from chronic headache 12 months after they took part in either a teleconsultation or a traditional consultation. This study found that patients who took part in traditional consultations more often consulted a general practitioner for headache during a one-year follow-up period (26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations